Status of Potential Non-Timber Forest Products for Wise Use and Conservation in the Langtang National Park’s Buffer Zone - Sharma, Bhuvan Keshar; Kandel, Ram Chandra (Journal of Natural History Museum, 2015)
Non-timber forest products are non-wooded biological resources derived from both natural and managed forests and other wooded areas. The objective of the study was to perform resource assessment for baseline information on the status and distribution of locally prioritized plant based non-timber forest products in Nuwakot and Sindhupalchok districts of Langtang National Park’s buffer zones. Consultative workshops and forest inventory techniques were applied to collect data. From the consultative workshops 133 species of plants having use value were identifi ed. It was identifi ed that Gaultheria fragrantissima and Edgeworthia gardneri were more potential species for commercial production and utilization. For commercial production and collection of Gaultheria fragrantissima, buffer zone areas of Nuwakot district will be the better place. Similarly, the commercial production and collection of Edgeworthia gardneri will be better in buffer zone areas of Sindhupalchok district. J. Nat. Hist. Mus. Vol. 28, 2014: 102-117